Effects of a pharmacist-managed anticoagulation outpatient clinic in Taiwan: evaluation of patient knowledge, satisfaction, and clinical outcomes. Issue 8 (17th November 2021) - Lin, Shin-Yi; Chen, Yi-Wen; Kang, Hao-Cheng; Wu, Yee-Jen; Chen, Pin-Zi; Wu, Chia-Wei; Lin, Chii-Shan; Wu, Fe-Lin Lin; Shen, Li-Jiuan; Huang, Yen-Ming; Huang, Chih-Fen
ABSTRACT: Objective: The study aimed to evaluate the improvement of patient knowledge of warfarin use, satisfaction with pharmacists, and the quality of international normalized ratio (INR) control after the implementation of an anticoagulant clinic (ACC) service. Methods: This was a prospective single-group pre- and post-comparison study. Patients who were at least 20 years of age and participated in a pharmacist-managed ACC service were enrolled from February 2012 to September 2015. Each participant completed a self-administered questionnaire before and after the ACC service to evaluate changes in warfarin knowledge. Another questionnaire was distributed after the ACC to evaluate participants' satisfaction with the pharmacist service in the ACC. The INR levels before and after the ACC intervention were obtained to calculate the proportion of time spent in the therapeutic INR range (time in therapeutic range, TTR). Paired t-tests were used to compare changes in participants' knowledge related to warfarin use. Multiple linear regressions were performed to explore the predictors associated with the participants' knowledge scores and TTR after the ACC intervention. Results: One hundred and forty-eight participants were enrolled in this study. A significant improvement (31.5%, p<0.001) in the knowledge of warfarin use was observed at the end of the ACC intervention. The interaction between warfarin and food was the most confusing factor for participants in warfarin use. More than 95% of the participants perceived a positive value of the pharmacist-managed ACC service. However, the consultation fee was the least satisfactory of the ACC service. The average TTR increased from 51.0±34.3% to 78.6±24.5% (p<0.001) after the ACC service was implemented. Participants' education levels and baseline knowledge scores were significant determinants associated with the knowledge improvement in the appropriate warfarin use (p<0.001). Conclusions: A pharmacist-managed ACC improved patient knowledge of warfarin use and INR control, and led to high satisfaction with the pharmacist service in the ACC in Taiwan. Pharmacists should focus on patients with lower education levels to facilitate their understanding of the appropriate warfarin use for better health outcomes.